Anesthetic concerns for pediatric patients in the era of COVID‐19. Issue 7 (5th June 2020) - Soneru, Codruta N.; Nunez, Karyn; Petersen, Timothy R.; Lock, Richard
Abstract: After a novel human coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), was reported in China in December 2019, the disease quickly reached pandemic level. On January 30, 2020, the World Health Organization (WHO) declared that the SARS‐CoV‐2 outbreak constituted a Public Health Emergency of International Concern. The caseload has increased exponentially, with WHO reporting 182 000 global cases by March 17, 2020, and over 2.6 million by 23 April. The clinical situation is complex, with children presenting different clinical features compared to adults. Several articles with recommendations on the anesthetic management of adult patients with COVID‐19 have been published, but no specific recommendations for pediatric anesthesiologists have been made yet. This article addresses specific concerns for the anesthetic management of the pediatric population with COVID‐19.